Learning with concept maps versus learning with classical lecture and demonstration methods in neuroanatomy - a comparison - Mahindra Kumar Anand; O1ive Singh; Prabhjot Kaur Chhabra (Wolters Kluwer Medknow Publications, 2018)
Aims and Objectives: Concept maps as learning tool facilitate development of meaningful learning. It was developed by Novak and Gowin and is based on Ausubel's theory of meaningful learning. Present study was undertaken to sensitize students to use concept maps as a learning tool and to assess its effect on learning. The objectives of the study were to compare the learning with concept maps and traditional lecture-demonstration methods in neuroanatomy. Materials and Methods : A randomized cross sectional prospective study was conducted on 60 medical students of 1st year. Students were divided into 3 groups A, B and C. Group A studied "spinal cord and its meninges" by developing concept maps. Group C learnt through lecture and demonstration method. Group B studied with readymade concept maps, lecture and demonstration methods. Pre and post test were conducted for all groups with pre validated questionnaire. Feedback was obtained from both students and faculty through a 5 point Likert scale. Paired and unpaired t test were applied for statistical analysis. Results: There was significant improvement in knowledge in group A students in comparison to group C and B students. This improvement was more marked with regards to high cognitive type MCQs. 80% students found that development of concept maps helped them to understand topic better but it was time consuming. Conclusion: Concept mapping is a better learning tool in comparison to classical lecture and demonstration method. It facilitates higher cognitive learning. It can be included in medical undergraduate curriculum to facilitate meaningful learning.